Methods of the Fire Maps for Nineteenth Century, İstanbul - Gürses Söğüt, Sibel (ICONARCH International Congress of Architecture and Planning, 2017)
Istanbul had to combat fires ever since the Byzantine period. The city which was rebuilt in accordance with the original architectural designs in the early Ottoman period went through a structural change in the 19th century due to the adaptation of modern reconstruction implementations. İt will be analysed in this text that the technic and the logic of the planning of the fire maps depicted fired places in the 19th century’s İstanbul. The fire maps of this period also contain proposals that have been drawn over the places destroyed by fires. Therefore, mapping based on the measurement information on the same graphic plane was realized. These cultural accumulations which date back approximately hundred and fifty years and which have retained the seals of the idea and the seal of the cartographer are the sole witnesses of the reconstruction of Istanbul. On the other hand, traditional Ottoman cities were not set up according to any preconceived idea or executed according to plans based on such designs. Nevertheless, it cannot be claimed that Ottoman architecture was realized without drafts or designs. Hence, the application of drafts on paper in the early period requires a distinct form of reading. For example, there are some parts in miniatures depicting early period Ottoman city topography that reflect imaginary additions of the artist, which are not even remotely related to reality. In another example, with only a ground floor plan drawn on graph paper with no cross section designs, final aspect or measurements could be transformed into a bathhouse or a mausoleum under the supervision of a construction supervisor. However, the scale maps of the 19th century, which bear the seal of both the architect and the authorizing institution and which were designed for designated places, demonstrate that the modernization period architecture was produced with very different techniques and for very different purposes.